Optimalisasi Penta Helix Collaboration Dalam Meningkatkan Prestasi Madrasah: Sinergi Untuk Pendidikan Karakter Berkualitas - Nasrun, Hasnan (Institut Riset dan Pengembangan Indonesia, 2024)
Abstract This study examines the application of the Penta Helix Collaboration concept in an effort to improve achievement at MTs Negeri 2 Deli Serdang, which is a pilot project of the Kurikulum Merdeka in Deli Serdang Regency. The main focus of this research is to understand how collaboration between five elements—government, academia, business, society, and the media—can improve the quality of education and student achievement. Through a descriptive qualitative method, this study collected data through interviews and document analysis, which showed that this collaboration succeeded in improving educational facilities and infrastructure, as well as creating stronger support from the community and students' parents. The results of the study show that each element has a unique role that complements each other in achieving a common goal, despite being faced with challenges such as a lack of understanding and resources. The resulting recommendations emphasize the importance of consistency in collaboration and strengthening communication between elements to achieve continuous improvement in achievement. This research makes a significant contribution to the development of a collaboration-based education model in madrasah.